2009
DOI: 10.1097/rct.0b013e31819f1b83
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Imaging of the Renal and Adrenal Lesions

Abstract: Our findings show that ADC measurement has a potential ability to differentiate benign and malignant focal renal and adrenal lesions with the guidance of conventional sequences. When used alone, diffusion-weighted imaging may lead to misdiagnoses due to overlapping ADCs of the lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 15 publications
2
29
0
Order By: Relevance
“…DWI and DTI have been used to examine a variety of intra-abdominal organs, including the liver, kidneys, and pelvic organs (7,8,12,15). With respect to the adrenal gland, only DWI data have been published (5,11,16). To the best of our knowledge, there has been no published study that employed DTI to study the adrenal glands.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…DWI and DTI have been used to examine a variety of intra-abdominal organs, including the liver, kidneys, and pelvic organs (7,8,12,15). With respect to the adrenal gland, only DWI data have been published (5,11,16). To the best of our knowledge, there has been no published study that employed DTI to study the adrenal glands.…”
Section: Discussionmentioning
confidence: 96%
“…When deciding the optimal b value for our study, we reviewed previous studies with b values ranging from 50 to 1000 s/mm 2 . In these studies, the range of observed ADCs was between 0.85 and 2.82×10 -3 (5,11,16). The optimal b value of a given tissue can be determined from the fact that b×ADC is equal to 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High ADC on the side of the cortex can be explained pathologically by dilation of the collecting ducts and aggregation of cystic structures. On the other hand, the ADC on the side of the papilla was relatively low and rather similar to those of solid masses like renal cell carcinoma or angiomyolipoma, 12 though the imaging parameters and methods used to calculate ADC diŠered somewhat. Thisˆnding may re‰ect clotted blood in cystic structures, or increased cellularity of the interstitium around the cysts.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis, Li et al [19] has shown a potential future role for this type of sequence to assess for cancers within the liver. Numerous lesions within the genitourinary organs (kidneys, ureters, bladder, adrenal glands, uterus, ovaries, and prostate), as well as the adrenal glands, may also eventually be evaluated for malignant potential using similar techniques [12,[20][21][22][23] . Recently, Padhani et al [24] and Koh et al [25] have alluded to the promising future of DWI as a cancer biomarker in monitoring response to chemotherapeutic agents, in tumor staging, and possibly to aid in antineoplastic clinical drug development.…”
Section: Introductionmentioning
confidence: 99%